Contradictory Aspects of Organized Youth Sport: Challenging and Fostering Sibling Relationships and Participation Experiences. (November 2014) - Trussell, Dawn E.
This article presents findings from an interpretive study that sought to understand how organized sport at the community level influences sibling relationships and interactions. The meanings of the participants' sport involvement, in relation to their siblings', was also examined using a constructivist approach to grounded theory. Nineteen youth (9 boys and 10 girls) from 7 different families living in a rural community in Canada participated in the study. The findings call attention to the significance of organized youth sport to enhance opportunities to spend time together, to shape perceptions of fairness and equality, and the implications that occur when living with a star athlete. Emphasis is placed on the contradictory nature of organized youth sport to strengthen and challenge sibling relationships as well as the potential of sibling dynamics to alter the nature of the participation experiences.